Interplay of fibroblasts with anaplastic tumor cells promotes follicular thyroid cancer progression - Fozzatti, Laura (2019)
Thyroid cancer is the most common endocrine malignancy. Anaplastic thyroid cancer is one of the most aggressive thyroid tumors. It is known that activation of oncogenes and/or inactivation of tumor suppressor genes in tumor cells promotes tumorigenesis. The microenvironment of the tumor also plays a key role on cancer development and progression in a variety of tumors. However, the mechanisms by which tumor-stroma crosstalk in thyroid cancer remains poorly characterized. In this study we aimed to understand how interactions between fibroblasts and anaplastic thyroid cancer cells contribute to thyroid carcinogenesis. We first characterized the phenotypic changes of human fibroblasts in vitro through co-cultures by using transwells as well as by using anaplastic thyroid cancer cells-derived conditioned media. We found that fibroblasts acquired an activated phenotype or also known as cancer-associated fibroblast phenotype after being in contact with soluble factors secreted from anaplastic thyroid cancer cells, compared to the fibroblasts in mono-cultures. All the changes were partly mediated through Src/Akt activation. Treatment with the antioxidant N-acetyl-cysteine reversed in part the metabolic phenotype of activated fibroblasts. Remarkably, conditioned media obtained from these activated fibroblasts promoted cell proliferation and invasion of follicular thyroid cancer cell line, FTC-133 cells. Thus, a reciprocal and dynamic interaction exists between tumor and stromal cells, which results in the promotion of thyroid tumorigenesis. The present studies have advanced the understanding of the molecular basis of tumor-stroma communications, enabling identification and targeting of tumor-supportive mechanisms for novel treatment modalities.